Contribution of rare coding variants to microcephaly in individuals with neurodevelopmental disorders - Jihoon G. Yoon; Hyunsoo Jang; Seungbok Lee; Se Song Jang; Soojin Park; Jaeso Cho; Minji Kim; Jiye Han; Hyounji Yun; Man Jin Kim; Soo Yeon Kim; Woo Joong Kim; et al. (Genome Medicine)
Abstract Background Microcephaly, characterized by an abnormally small head size, frequently co-occurs with neurodevelopmental disorders (NDDs). While the genetic basis of NDDs has been widely investigated, the contribution of rare coding variants to microcephaly remains poorly understood. Methods We investigated the relationships between head circumference and rare coding variants in 418 individuals with microcephaly, analyzing data from 1050 exomes (312 trios and 106 proband-only samples). Participants were classified into primary microcephaly (PM) and secondary microcephaly (SM) groups, and their clinical and genetic characteristics were systematically assessed. The functional impact of high-priority candidate genes, RTF1 and ASAP2, was further validated using neural progenitor cells (NPCs) and human forebrain organoid models. Results Exome sequencing revealed 142 causative and 12 candidate genes associated with microcephaly. Pathway analyses indicated that PM genes are linked to early phases of brain development, whereas SM genes are more associated with later stages of neuronal maturation. In addition, the PM group had a significantly higher proportion of autosomal recessive disorders and exhibited more severe microcephaly than the SM group. Notably, females displayed greater microcephaly severity than males, primarily attributable to differences in the origin of the allele and inheritance patterns on the X chromosome. Functional experiments using CRISPR-Cas9 knockout in NPCs and brain organoids demonstrated reduced NPC proliferation, supporting the essential role of RTF1 and ASAP2 in brain development. Conclusions This study sheds light on the complex genetic architecture of microcephaly, emphasizing the impact of rare coding variants on brain development and delineating distinct clinical and molecular profiles underlying PM and SM.